Interplay of charge density and relative humidity on the structure of nitrate layered double hydroxides - Jobbagy, Matias (2010)
The structure of several crystalline Ni(II)-Al(III) and Mg(II)-Al(III) layered double hydroxides (LDHs) intercalated with nitrate anions was studied as a function of the relative humidity. For low charge density LDHs, the electrostatic attraction between the anions and the positive LDH layers prevails over any other interaction, and the anions remain flat, F, with their C 3 axis perpendicular to the xy planes, irrespective of water activity. For LDHs bearing higher charge densities, the incoming water molecules drive an abrupt phase expansion in which the anions tilt their C3 axis with respect to the interlamellar xy plane, thus resulting in an expanded, T, form. The structural F-T transition is discontinuous, and involves a second staging phase intermediate, with alternated F and T galleries. For intermediate charge density LDHs, the hydration process easily reverts, once the samples are resubmitted to a dry atmosphere. Dehydration of high charge density LDHs is however kinetically hindered; this behavior is explained in terms of the structural features of the involved phases. For all samples, the maximum net gallery expansion is proportional to the layer charge density, irrespective of the nature of the divalent cation. © 2010 American Chemical Society.